Mental Health Challenges in Children: A Cross-Sectional Study Using the Strengths and Difficulties Questionnaire - Ipah Saripah; Lucky Angkawidjaja Roring; Rifqy Muhammad Hamzah; Tb. Moh. Irma Ari Irawan; Dody Hartanto; Nadia Aulia Nadhirah; Diana Lea Baranovich; Hoeur Sethul (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Mental health of elementary school students is an important issue that needs attention in efforts to improve individual well-being and development. This study aims to identify the mental health profile of elementary school students in West Java through the use of the Strengths and Difficulties Questionnaire (SDQ). The study employs a cross-sectional design involving 889 elementary school students as research subjects. Data were collected through the distribution of the SDQ questionnaire both online and offline. Data analysis was conducted using descriptive statistics to describe the distribution of scores on each SDQ subscale. The analysis results of the instrument reveal the prevalence of emotional symptoms, conduct problems, hyperactivity, peer relationship problems, and prosocial behavior in elementary school students. The findings of this study are expected to serve as a foundation for policymakers, educators, and parents in designing more effective programs to improve students' mental health and prevent the emergence of more serious psychological issues.